2020
DOI: 10.13106/jafeb.2020.vol7.no4.97
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Capital Structure on Firm Performance: Evidence from Vietnam

Abstract: This paper explores the impact of capital structure on firm performance in the context of Vietnam. The paper investigates the different effect of capital structure on firm performance in state-owned and non-state enterprises listed on the Vietnam stock market. The panel data of research sample includes 488 non-financial listed companies on the Vietnam stock market for a period of six years, from 2013 to 2018. The Generalized Least Square (GLS) is employed to address econometric issues and to improve the accura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
74
2
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(97 citation statements)
references
References 39 publications
13
74
2
8
Order By: Relevance
“…Therefore, only when the capital demand exceeds the supply capacity from the content capital, the enterprise can mobilize from the loan. This is also consistent with the study of Baral (2004), Akhtar (2005), Gurcharan (2010), Shubiri (2010), Akinlo (2011), Sharif et al (2012), Nguyen and Nguyen (2020).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Therefore, only when the capital demand exceeds the supply capacity from the content capital, the enterprise can mobilize from the loan. This is also consistent with the study of Baral (2004), Akhtar (2005), Gurcharan (2010), Shubiri (2010), Akinlo (2011), Sharif et al (2012), Nguyen and Nguyen (2020).…”
Section: Discussionsupporting
confidence: 91%
“…They argue that a profitable enterprise tends to mobilize internal rather than external resources, and firms often reduce debt. This negative relationship can be found in the study of Baral (2004), Akhtar (2005), Gurcharan (2010), Shubiri (2010), Akinlo (2011), Sharif et al (2012), Nguyen and Nguyen (2020). The hypothesis is as follows: H 1 : Profitability of listed construction companies is negatively correlated with capital structure.…”
Section: Hypothesesmentioning
confidence: 91%
“…Different kinds of literature support the strong influence of leverage on a firm's profitability. According to some studies regarding leverage and profitability, both variables move oppositely, which means they are negatively associated (Muritala, 2012;Salim and Yadav, 2012;Soumadi and Hayajneh, 2012;Abdel-Jalil, 2014;Hasan et al, 2014;Ramadan and Ramadan, 2015;Siddik et al, 2017;Nguyen and Nguyen, 2020). Here, capital structure is calculated as:…”
Section: Capital Structurementioning
confidence: 99%
“…According to Berger and Patti (2006), financial leverage has a positive effect on dependent variables about financial performance. On the other hand, Astami et al (2010), Chu Thi Thu Thuy et al (2015, Nguyen and Nguyen (2020) suggested that financial leverage has negative impact on financial performance. However, according to Alipour (2012), financial leverage has a positive impact on ROE and negative impact on ROA and ROS.…”
Section: H6: Liquidity Has a Positive Impact On Financial Performancementioning
confidence: 99%